Identifying the effective factors in the proper estimation of the time and cost of completion of construction projects using factor analysis (Case study: commercial and residential buildings in Arak) - Sayad Hamid Lajevardi; Mohammad Fallah; Mohsen Soleimani (مهندسی و مدیریت ساخت, 2023)
Today, forecasting the actual costs of a project over a period is one of the fundamental aspects of project management. This is especially critical for construction projects, which play a significant role during natural crises. Effective cost and time management are crucial factors in the optimal execution of these projects. This study aims to identify the key factors influencing the accurate estimation of time and cost for construction projects using factor analysis. The case study focuses on commercial and residential buildings in the city of Arak. The study is applied in nature and employs an exploratory research method. The statistical population includes all senior managers, supervisors, and engineers from the Arak Engineering System Organization, with 170 individuals selected through a convenience sampling method. A factor analysis model was used to examine the relationships between various components. The results indicate that the most significant factors affecting accurate time and cost estimation include: failure to resolve objections promptly (factor load: 9.14), delays in preparing necessary maps during execution (factor load: 6.66), insufficient budget provision at the right time (factor load: 5.94), lack of practical and executive vision among designers (factor load: 5.85), serious errors in project design and contract documents (factor load: 4.04), inadequate planning for changes (factor load: 3.88), absence of a basic unit price list for inner-city works (factor load: 3.83), and project suspension by other institutions and organizations (factor load: 3.78). These factors were identified as the most critical for accurate time and cost estimation in the construction of commercial and residential buildings in Arak.